PENCEGAHAN TINDAK PIDANA TERHADAP ANAK BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK OLEH KEPOLISIAN SEKTOR BANGKO PUSAKO ROKAN HILIR - Artina, Dessy; ', Almizan; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Implementation of child protection in the territorial waters of the Bangko Pusako Sector Police has not been maximally protection for children still the number of children who become victims of crime, in contrast to those already regulated in the Act. Therefore, the purpose of writing this thesis, namely: first, how the implementation of prevention of crime against children based on Law number 35 year 2014 about the amendment to Law number 23 year 2002 about child protection by Police Sector Bangko Pusako Rokan Hilir. Second, what are the obstacles in implementing prevention of crime against children based on Law number 35 year 2014 regarding the amendment to Law number 23 year 2002 concerning child protection by Police Sector of Bangko Pusako Rokan Hilir. This type of research can be classified in the type of sociological law research, because in this study the authors directly approach the way by looking in terms of legislation and the reality that looks at the object of research. The author conducted this research in the Police Sector Bangko Pusako. Population and sample of this research are Kapolsek Bangko Pusako, Reskrim Criminal Polsek Bangko Pusako, Victim's Parent and / or Victim's Legal Counsel. Sources of data used are: primary data and secondary data. Data collection techniques in this study with interviews, observation, and literature review. The conclusions obtained from the results of this study are first, the implementation of prevention of crime against children based on Law number 35 year 2014 on the amendment of Law number 23 year 2002 on child protection by Police Sector Bangko Pusako Rokan Hilir not fully in accordance with what expected by the community and the aspiration of the law because the efforts undertaken by the police have not been maximized and can not touch all levels of society as a whole. Second, obstacles in the implementation of prevention of crime against children based on Law number 35 year 2014 about the amendment of Law number 23 year 2002 concerning child protection by Police Sector of Bangko Pusako Rokan Hilir Sector ie society factor, facility factor and infrastructure, personnel and geographical factors.Keywords: Prevention-Crime-Against Child-Police Sector Bangko Pusako.